Asumsi Terhadap Manusia Sebagai Kelompok Dalam Pengembangan Organisasi Di SD Pembangunan Laboratorium, Kota Padang - Mila Wati (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
This study aims to analyze assumptions about humans as groups within the context of organizational development at SD Pembangunan Laboratorium, Padang City. The research focuses on how group behavior, motivation, and interpersonal relationships influence the school’s organizational effectiveness. A qualitative descriptive approach was employed, using observation and interviews with teachers and educational staff. The results indicate that positive social interaction, purposeful collaboration, and open communication among group members significantly contribute to a productive work environment. Moreover, shared awareness of organizational goals enhances each member’s sense of responsibility and engagement. The findings emphasize that the success of educational organizational development is strongly determined by the quality of human relationships within working groups.